Enhancing Employees’ Collaboration Through Trust in Organizations: (An Emerging Challenge in Human Resource Management) - Tariq, Amber; Aslam, Hassan Danial; Habib, Muhammad Badar; Siddique, Anam; Khan, Mannan (Mediterranean Journal of Social Sciences, 2012)
Trust has been recognized as a multi-dimensional concept with its various components. However, the missing link oftrust and collaboration is still being observed in human resource management literature. This study deliberates upon exploringthe linkage between trust and collaboration among employees in an organization. The current research highlights the positivecontribution of trust in building and sustaining collaboration in the organizations. Researchers have elaborated a detailed metaanalysisof literature on trust and collaboration in order to achieve its effectual link with organizational performance. The findingsreveal that trust and collaboration are interdependent processes. Trust is an essential element in building collaboration and highlevel of trust is required to build effective collaborative relationships.